Ambient energy harvesting for self-powering devices - Lim, Benedict Sheng (2017)
As the demand for energy increases, there has been a surge of research to harvest energy freely from air. Due to the wirelessly connected world, RF (radiofrequency) energy can be easily collected, stored and later used to power up devices or even household appliances. As a matter of fact, a number of low powered, battery applications are already in use such as RFID tags and contactless smart cards. With the advent of technology, harvesting and converting these energies for storage and charging portable devices or household appliances can be realized in the near future. The purpose of the project is to design a RF to DC converter using a Dickson charge pump topology to convert a 900 MHz input AC voltage of 0.3V to an output DC voltage of 1.8V. In order to achieve the stated goal, firstly the charge pump must be tuned to the operating frequency of 900 MHz. Secondly, an impedance matching circuit must be added so as to maximize the input power and reduce reflected power. This paper looks into the original setup of a Dickson charge pump which functions mainly as a DC to DC converter or boost converter which increases the input voltage to a higher level at the output. Subsequently, a modified Dickson charge pump is introduced and test first as an AC to DC converter with lower frequency components by connecting it to a function generator to ensure that the pump topology is able to increase its voltage. An RF modified Dickson charge pump is further design and constructed. 2 boards of different frequencies are built, 1 is 540 MHz which is around TV signal band and 900 MHz which is GSM band to compare the power collected at each frequency and component values. The latter is proven to be a more practical solution and the rationale will be further discussed in this paper.